Shedding Light: The Role of Public Utility Commissions in Encouraging Adoption of Energy Efficient Lighting by Low-income Households - Liang, Angelina (Columbia Journal of Environmental Law, 2019)
This Note proposes harnessing the abilities of state public utility commissions (“PUCs”) to tailor preexisting efficient lighting programs for low-income households, which are particularly susceptible to the common barriers to efficient lighting adoption. Although the exact mandate differs by state, most PUCs regulate and monitor utility services and ensure reliable delivery of electricity at just and reasonable rates. Within this relatively undefined area, PUCs may extend the scope of their rules to encompass energy efficiency schemes by characterizing such programs as a method of promoting the reliability and decreasing the costs of the entire electricity grid. This Note identifies three approaches that, if applied together, accommodate for special needs of low-income households and satisfy general policy goals: free and subsidized light bulbs, free audits, and educational projects. The combination of these approaches is low-cost and self-sustaining: PUCs already regulate utilities, meaning no additional procedure or oversight is necessary, and reduced electricity bills, once initial barriers are overcome, will likely compel consumer adoption without significant funding from the state. Using no more than their currently vested powers, PUCs may significantly influence efficient lighting adoption rates by low-income households and thereby generate low-cost, system-wide benefits for those individuals, the state electricity grid, and the global environment. This Note focuses primarily on New York’s PUC as a promising example of the potential for such a program.